Dengue Virus Infection Causes the Activation of Distinct NF-κB Pathways for Inducible Nitric Oxide Synthase and TNF-α Expression in RAW264.7 Cells. (14th June 2015) - Cheng, Yi-Lin; Lin, Yee-Shin; Chen, Chia-Ling; Wan, Shu-Wen; Ou, Yi-Dan; Yu, Chia-Yi; Tsai, Tsung-Ting; Tseng, Po-Chun; Lin, Chiou-Feng
Abstract : Infection with dengue virus (DENV) causes an increase in proinflammatory responses, such as nitric oxide (NO) generation and TNF- α expression; however, the molecular mechanism underlying this inflammatory activation remains undefined, although the activation of the transcription factor NF- κ B is generally involved. In addition to TNF- α production in DENV-infected murine macrophage RAW264.7 cells, inducible NO synthase was transcriptionally and posttranslationally elevated and accompanied by NO generation. NF- κ B is known to be activated by DENV infection. Pharmacologically inhibiting NF- κ B activation abolishes iNOS/NO biosynthesis and TNF- α production. With inhibition, the potential role of NF- κ B in oxidative signaling regulation was prevented during DENV infection. Heat-inactivated DENV failed to cause the identified inflammatory responses. Pharmacological inhibition of TLR3 partly decreased NF- κ B activation; however, it effectively abolished inducible iNOS/NO biosynthesis but did not inhibit TNF- α production. In contrast to TLR3, viral protein NS2B3 also independently contributed to NF- κ B activation to regulate TNF- α production. These results show the distinct pathways for NF- κ B activation caused by DENV infection individually for the regulation of iNOS/NO and TNF- α expression.